METHODS OF APPLYING ARTIFICIAL INTELLIGENCE FOR ANALYZING SOCIO-ECONOMIC DATA IN PUBLIC ADMINISTRATION - Ardelian, Ivan; Pletsan, Khrystyna (Public Management and Policy, 2025)
The article provides a systematic analysis of contemporary approaches to the application of artificial intelligence (AI) technologies in the field of public administration, with a particular focus on the processing and interpretation of socio-economic data that underpin government decision-making. The study outlines the methodological foundations for integrating intelligent information systems into the functioning of public authorities under the conditions of ongoing digital transformation and the increasing need for data-driven governance. Special emphasis is placed on the practical use of tools such as machine learning, neural networks, natural language processing, geographic information systems, and other intelligent data analysis instruments. The paper identifies key vectors for the implementation of AI-based solutions in the development of public policy, forecasting socio-economic dynamics, optimizing budget expenditures, and enhancing the quality and accessibility of administrative services. A comparative analysis of international case studies is conducted to examine successful examples of AI integration in government services and to evaluate their relevance and applicability to the Ukrainian context. The role of Administrative Service Centers (ASCs) is highlighted as a strategic entry point for the deployment of AI technologies in the interface between the state and its citizens. The article concludes with a conceptual model for the phased introduction of AI tools into the infrastructure of public administration, incorporating regulatory, ethical, organizational, and cybersecurity considerations. The research contributes to the understanding of the benefits and limitations of AI adoption in governance and identifies future research priorities related to the institutional modernization of public administration systems through intelligent digital technologies.